1998
DOI: 10.1074/jbc.273.15.8659
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structure of the Nicotinic Acetylcholine Receptor Ion Channel with the Uncharged Photoactivable Compound [3H]Diazofluorene

Abstract: The nicotinic acetylcholine receptor (AChR) 1 isolated from the electric organ of the marine elasmobranch Torpedo californica is the best characterized member of a family of ligandgated ion channels which includes the ␥-aminobutyric acid, glycine, and serotonin 5-HT 3 receptors (for recent reviews, see Refs. 1-3). The AChR is composed of four homologous subunits (␣ 2 ␤␥␦) arranged quasi-symmetrically around a central cationselective ion channel (4). The subunits each have a characteristic topology as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 38 publications
3
67
1
Order By: Relevance
“…The M2 region alone is sufficient to form a chloride-conducting pore because synthetic M2-based peptides form Cl Ϫ -conducting channels when added to cells (24). Receptor topology was also probed using photoactivable lipophilic compounds to examine the protein-lipid interface of the nAChR (25). The periodicity of the labeled residues in M4 was consistent with a transmembrane ␣-helix with a face of the helix exposed to the acyl chains of the bilayer.…”
Section: Receptor Topologymentioning
confidence: 99%
“…The M2 region alone is sufficient to form a chloride-conducting pore because synthetic M2-based peptides form Cl Ϫ -conducting channels when added to cells (24). Receptor topology was also probed using photoactivable lipophilic compounds to examine the protein-lipid interface of the nAChR (25). The periodicity of the labeled residues in M4 was consistent with a transmembrane ␣-helix with a face of the helix exposed to the acyl chains of the bilayer.…”
Section: Receptor Topologymentioning
confidence: 99%
“…states, therefore suggesting that these domains display a substantial conformational change upon agonist-induced activation of the AChR (10,12,13,38,39). A recent study reported structural and conformational changes in the third transmembrane domain of a homologous receptor, the ␣M3 domain of the ␥-aminobutyric acid type A receptor (40).…”
mentioning
confidence: 99%
“…Additionally, residues localized to the transmembrane domains of these receptors have been identified by cysteine scanning methods (for review see Ref. 22) as well as using lipophilic cross-linking agents (23)(24)(25). However, despite these and other studies on nAchR and other members of this neuroreceptor superfamily, the details of the molecular architecture of these ion channels remain refractory and subject to debate (for review see Ref.…”
mentioning
confidence: 99%